COVID-19 pandemic and illicit drugs - Alessandra Liquori O’Neil (Freedom from Fear, 2020)
Since the beginning of the Covid-19 pandemic, no clear evidence has emerged of a significant decrease in the supply of drugs at the global level, including in Italy, even after the quarantine was extended to the entire country.